2022
DOI: 10.1111/cpf.12780
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac remodelling in association with left ventricular dyssynchrony and systolic dysfunction in patients with coronary artery disease

Abstract: Background In patients with coronary artery disease (CAD), ischaemic cardiomyopathy may result in progressive cardiac remodelling and left ventricular (LV) dysfunction. Myocardial perfusion imaging (MPI) can be used to quantify LV size and shape, mechanical dyssynchrony (LVMD) and ejection fraction (EF) as well as myocardial ischaemia and injury extents. We investigated the prevalence of LV remodelling (LVR) in patients with CAD and the relationship between LVR, LVMD and EF. Methods Three hundred twenty‐six pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Research has shown that anti-TNF therapy can effectively improve cardiovascular function [ 26 ], which further illustrated the damage of inflammatory response to myocardial function. EDV is the most useful clinical variable for diagnosing left ventricular remodeling (LVR) [ 27 ]. The elevated of LVEDV might indicate the presence of LVR in AD pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that anti-TNF therapy can effectively improve cardiovascular function [ 26 ], which further illustrated the damage of inflammatory response to myocardial function. EDV is the most useful clinical variable for diagnosing left ventricular remodeling (LVR) [ 27 ]. The elevated of LVEDV might indicate the presence of LVR in AD pregnant women.…”
Section: Discussionmentioning
confidence: 99%